An Exploration of Nature-Related Financial Risks in Malaysia - World Bank (World Bank, Washington, DC, 2022)
Malaysia is one of the world's megadiverse countries, and many of its economic activities are directly or indirectly dependent on nature and its associated ecosystem services.' The Coronavirus (COVID-19) pandemic, with its far-reaching economic impacts, is a reminder of the link between human health and planetary health, given that most human infectious diseases are transmitted between species. In parallel to climate-related risks, nature-related risks can lead to economic and financial losses. Central banks have recently started to investigate biodiversity and other nature-related impacts and dependencies of financial systems. The NGFS, of which Bank Negara Malaysia (BNM) is a member, has recommended several first actions that could be taken by financial sector regulators and supervisors to help build the foundations for more comprehensive measures. BNM, as part of its mandate to promote monetary and financial stability conducive to the sustainable growth of the Malaysian economy, has an interest in understanding nature-related financial risks to the financial sector. to the financial sector. A better understanding of nature-related financial risks is important for prudential supervision to identify and address any emerging risks in the loan books and investments of banks and other financial institutions. This report assesses the exposure of Malaysian banks to sectors and regions that are highly vulnerable to nature-related risks. This study makes use of both Malaysian and global data.